Alzheimer's disease patients getting lost in the community: Is road network structure a significant risk factor?: Neuropsychiatry and behavioral neurology/Assessment/Measurement of neuropsychiatric/Behavioral and psychological symptoms. (7th December 2020) - Puthusseryppady, Vaisakh; Manley, Ed; Hane Aung, Min; Patel, Martyn; Hornberger, Michael
Abstract: Background: Getting lost is one of the earliest and most distressing symptoms seen in Alzheimer's disease (AD). Despite being a prevalent problem in the community worldwide, very few studies have explored real‐world environmental factors that may potentially contribute to patients getting lost. In this study, we aim to investigate whether road network structure plays a contributory role to AD patients getting lost in the community using retrospective and prospective data. Method: Retrospective data of police case records of a large sample of missing dementia patients in the Norfolk county (n = 210), over a three year period, was used first to test our aim. Here, for each missing patient location, we measured the road intersection density, intersection complexity, as well as orientation entropy at a 1 km radius buffer zone around these locations; these measures were then compared to that of a set of random but matched locations. We then collected data prospectively to test the performance of 18 community‐dwelling patients with AD (aged 50‐80 years) on their ability to find their way in their own neighbourhood using a novel 'Detour Navigation Task'. Here, we will measure the road intersection density, complexity, and orientation entropy at the locations in their neighbourhood where patients exhibited spatial disorientation. Result: The 210 patients in the police data went missing from a total of 168 locations in the Norfolk county. Our results show that the locations patients went missing from had significantly increased road intersection density, complexity, and orientation entropy when compared to that of the matched locations. Meanwhile, the performance of the sample of 18 AD patients on the Detour Navigation Task will then be analysed to see whether the neighbourhood locations where the patients felt disoriented exhibited higher road intersection density, complexity, and orientation entropy when compared to locations where they did not feel disoriented. Conclusion: The results of this study will provide evidence for road network structure as being a significant factor contributing to AD patients getting lost. This can in future help to potentially identify patients at high risk for getting lost as well as inform safeguarding guidelines.